Dari Objek Kekuasaan ke Subjek Perlawanan: Agensi Perempuan dalam Lakon Kethoprak Rara Mendut-Pranacitra - Ningsih, Santini Ayu; Purnomo, Sucipto Hadi; Widagdo, Sungging (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2025)
Traditional kethoprak performances often portray women as passive figures, but the play Rara Mendut-Pranacitra challenges this by presenting an active female protagonist. This study analyzes how the central character, Rara Mendut, demonstrates female agency by fighting for her desires and freedom against a patriarchal social structure. Using a qualitative, descriptive-analytical approach grounded in Anthony Giddens's theory of agency, the research examines specific dialogues and scenes from a performance available on the Balkam TV YouTube channel. The analysis reveals that Rara Mendut exhibits her agency through three key indicators: reflective agency (subtly rejecting marriage proposals), symbolic negotiation (using humor to challenge authority), and personal decision-making (gaining economic independence). Her ultimate act of agency is her radical choice to control her own destiny. The findings confirm that traditional performing arts can serve as a powerful medium for female resistance. This study demonstrates that female characters in Javanese narratives are not merely passive objects but active agents capable of shaping social structures from within, providing a valuable theoretical perspective beyond traditional feminist criticism.